The role of axonal Kv1 channels in CA3 pyramidal cell excitability - Sylvain Rama (Nature Portfolio, 2017)
Abstract Axonal ion channels control spike initiation and propagation along the axon and determine action potential waveform. We show here that functional suppression of axonal Kv1 channels with local puff of dendrotoxin (DTx), laser or mechanical axotomy significantly increased excitability measured in the cell body. Importantly, the functional effect of DTx puffing or axotomy was not limited to the axon initial segment but was also seen on axon collaterals. In contrast, no effects were observed when DTx was puffed on single apical dendrites or after single dendrotomy. A simple model with Kv1 located in the axon reproduced the experimental observations and showed that the distance at which the effects of axon collateral cuts are seen depends on the axon space constant. In conclusion, Kv1 channels located in the axon proper greatly participate in intrinsic excitability of CA3 pyramidal neurons. This finding stresses the importance of the axonal compartment in the regulation of intrinsic neuronal excitability.